The Report of the Attorney General's Committee on Antitrust Laws - Markham, Jesse W. (Quarterly Journal of Economics, 1956)
I. Introduction, 193. — II. The committee's recommendations for legislative change, 195. — III. The committee's recommendations to the judiciary and antitrust law enforcement agencies, 202; Sherman Act, 202; mergers and dissolution, 206; antitrust policy on distribution, 208; patents, 211. — IV. Some significant omissions, 213; oligopoly, 213; exemptions from antitrust policy, 214; antitrust administration, 215. — V. Summary, 215.